PENGARUH KEPEMIMPINAN SUPORTIF KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI SMP KABUPATEN LIMAPULUH KOTA - Evita Maila Sari; Tesi Eka Putri; Nurhizrah Gistituati; Rusdinal Rusdinal; Nellitawati Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the influence of supportive leadership by school principals and school culture on teachers’ performance in junior high schools in Limapuluh Kota Regency. The main issue addressed in this research is the variation in teachers’ performance, which is presumed to be influenced by differences in principals’ leadership styles and the strength of school culture in each educational institution. The study employs a qualitative approach using in-depth interviews with principals, teachers, and educational staff selected purposively. Data were analyzed through processes of reduction, presentation, and conclusion drawing using thematic analysis techniques. The findings reveal that supportive leadership by principals has a strong impact on improving teachers’ performance. Principals who demonstrate empathy, provide moral and professional support, and foster open communication are proven to enhance teachers’ motivation, self-confidence, and loyalty to their duties. Moreover, a positive school culture, characterized by values of cooperation, discipline, responsibility, openness, and appreciation for achievement, also contributes significantly to shaping professional and quality-oriented teacher performance. Both variables show a complementary and reinforcing relationship. Supportive leadership serves as a driving force for establishing a healthy school culture, while a strong school culture enhances the effectiveness of supportive leadership.